PERAN DUKUNGAN PERTEMANAN DAN KEPERCAYAAN DIRI TERHADAP TINGKAT KESEPIAN MAHASISWA - Juselda; Dewi, Fransisca Iriani Roesmala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study employed multiple regression analysis, which showed a coefficient of determination of R² = 0.339, indicating that friendship quality and self-confidence have a significant role in loneliness. Loneliness is a common experience felt by many individuals. Internal and external factors, such as self-confidence and friendship quality, can actively influence feelings of loneliness, especially among university students in the late-adolescence to early-adulthood period. During this stage, students face various demands, ranging from completing their education to expanding social relationships. The purpose of this study was to examine the role of friendship quality and self-confidence in loneliness among university students. This study used a quantitative approach with 164 student respondents. The instruments used included the Friendship Quality Scale (FQS), the Self-Confidence Questionnaire, and the UCLA Loneliness Scale Version 3. Data were analyzed using multiple linear regression with the assistance of SPSS version 27. The results showed that friendship quality had a more significant effect on loneliness (β = –0.365, p = 0.001 < 0.05) than self-confidence (β = –0.309, p = 0.001 < 0.05). Both variables simultaneously contributed to reducing loneliness levels. Although friendship quality had a stronger effect, the overall results indicate that both friendship quality and self-confidence play important roles in reducing loneliness among university students.